1977
DOI: 10.1021/ac50017a030
|View full text |Cite
|
Sign up to set email alerts
|

Computerized curve-fitting to determine the equivalence point in spectrophotometric titrations

Abstract: value). The derived reactivity ratio for butene, i.e., the reciprocal of the slope, 0.51, is quite reasonable in comparison with the literature value of 0.50 (28) reported for a related catalyst system, Et3A1/TiC13. However, much more data would be required for a satisfactory measure of this parameter.These materials were then used in the heated cell infrared method of Tosi et al. (8). The absorbances were recorded together with those obtained for a number of blends of polybutene and polypropylene homopolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Other investigators have also reported the application of nonlinear regression analysis to potentiometric and spectrophotometric data (II,13,116,132). use computer graphics to examine Gran plots and error functions in order to determine the equivalence point of potentiometric titrations.…”
Section: State and Parameter Estimationmentioning
confidence: 99%
“…Other investigators have also reported the application of nonlinear regression analysis to potentiometric and spectrophotometric data (II,13,116,132). use computer graphics to examine Gran plots and error functions in order to determine the equivalence point of potentiometric titrations.…”
Section: State and Parameter Estimationmentioning
confidence: 99%
“…Although computer simulation of acid-base pH titrations has been discussed for over 30 years in this Journal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and fitting experimental titration data to theoretical expressions has been discussed in the research literature (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), it is interesting to note fitting experimental pH titration data has received relatively little pedagogical attention. In a 1993 article, focusing on the development of a single closed-form expression for the titration curve for a variety of titrations, de Levie (8a) indicates fitting experimental titration data to a derived theoretical expression is possible.…”
mentioning
confidence: 99%
“…In recent years, there has been considerable interest in using computers for titrations, particularly where Gran plots (9), Hofstee plots (10), or modification of these (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) could provide improved determination of the equivalence point in potentiometric, spectrometric, and amperometric experiments. More recently, microcomputers have greatly increased the possibilities of improved automated titrations at modest cost.…”
mentioning
confidence: 99%